Festivalization of the City: Contemporary Examples - Karpińska-Krakowiak, Małgorzata (Lidé města, 2009)
There is unprecedented interest in festivals as a cultural phenomenon that contributes to urban images, identities, and myths. The article addresses the role of festivals as image building-blocks and specifies a number of success factors for festivals aspiring to become the means of urban image creation. Festivals integrate people and establish inner-communities; they induce commonly shared experiences and encourage an atmosphere of fun, pleasure and excitement. In this way festivals facilitate the processes of transferring pleasant experiences onto other subjects, places or phenomena related to them (i.e. onto a city). Festivals act as an urban image device. The purpose of this paper is to present another dimension of festivals and describe how they can perpetuate false notions and fake images about the hosting city. The example of the city of Lodz is described, where the Festival of Dialogue of Four Cultures creates an image of Lodz as a city of four cultures (which it was not) and a national and cultural melting pot (which it was not).